Multiple sclerosis with predominant, severe cognitive impairment - Staff, Nathan P. (2009)
OBJECTIVE: To describe the characteristics of multiple sclerosis (MS) presenting with severe cognitive impairment as its primary disabling manifestation. DESIGN: Retrospective case series. SETTING: Tertiary referral center. PATIENTS: Patients were identified through the Mayo Clinic data retrieval system (1996–2008) with definite MS (McDonald criteria) and severe cognitive impairment as their primary neurological symptom without accompanying significant MS-related impairment or alternative diagnosis for cognitive dysfunction. Twenty-three patients meeting inclusion criteria were compared regarding demographics, clinical course and radiological features. MAIN OUTCOME MEASURES: Demographic, clinical, and radiological characteristics of the disease. RESULTS: Twelve patients were men. The median age of the first clinical symptom suggestive of CNS demyelination was 33 years, and severe MS-related cognitive impairment developed at a median of 39 years. Cognitive impairment could be dichotomized as subacute fulminant (n=9) or chronic progressive (n=14) in presentation, which corresponded to subsequent relapsing or progressive MS courses. Study patients commonly exhibited psychiatric (65%), mild cerebellar (57%) and cortical symptoms and signs (e.g. seizure, aphasia, apraxia) (39%). Fourteen of 21 (67%), where documented, smoked cigarettes. Brain MRI demonstrated diffuse cerebral atrophy in 16 and gadolinium enhancing lesions in 11. Asymptomatic spinal cord MRI lesions were present in 12 of 16 patients (75%). Immunomodulatory therapies were generally ineffective in improving these patients. CONCLUSIONS: We describe patients with MS whose clinical phenotype is characterized by severe cognitive dysfunction and prominent cortical and psychiatric signs presenting as a subacute fulminant or chronic progressive clinical course. Cigarette smokers may be over represented in this phenotype.